Kajian Unsur Dramatik dan Estetika Taman Penasar Ceraken - I Komang, Prayoga Putra; Sedana , I Nyoman; , Dru Hendro (Pusat Penerbitan LP2MPP ISI Bali, 2025)
Taman Penasar is an artistic development derived from Pasantian, which integrates vocal performance, literature, acting, and traditional music played by 5-7 core performers. This performance serves not only as entertainment but also as a guide for social interaction. Unfortunately, despite its profound cultural values, it has received limited academic attention, such as the Taman Penasar performance titled Ceraken, which presents issues surrounding traditional Balinese medicine and the role of Balian (traditional healers), a topic of current discussion. This study aims to analyze the dramatic structure, aesthetic elements, and inherent values of the performance. A qualitative approach is used to descriptively present the findings, employing drama theory and aesthetic theory as analytical tools. The results of this study show that the dramatic elements of the performance are constructed through: 1) A plot based on contemporary societal issues; 2) A forward-moving narrative structure; 3) Characterization through new terms introduced in the performance, such as Panegteg, Panungkas, Panembang, and Paneges; 4) Setting conveyed through dialogue; 5) Dialogue that upholds the ethical use of the Balinese language. The aesthetic elements are built through the performance's integrity, emotional depth, harmony in costumes and movement, and the prominence of tembang (traditional songs), musical accompaniment, and acting. Additionally, the balance between tembang, musical accompaniment, Paneges, Panegteg, and Panungkas is emphasized. This performance also upholds religious, social, and educational values. Therefore, the researcher hopes that this performance will continue to thrive and attract public interest as a valuable medium for learning.